Massive pericardial effusion and short stature caused by autoimmune hypothyroidism in a 9-year-old girl - Yun Hee Gyon; Heon-Seok Han (Korean Society of Pediatric Endocrinology, 2015)
A 9-year-, 11-month-old girl was brought to the Emergency Department for sudden dyspnea caused by massive pericardial effusion. In addition to relative bradycardia despite impending cardiac tamponade, short stature, overweight, and hypercholesterolemia were clues for suspected hypothyroidism. During thyroxine supplementation, catch-up growth was incomplete by rapid skeletal maturation. The use of short-term growth hormone showed increased growth velocity. In conclusion, primary hypothyroidism should be included in the etiologic evaluation of pericardial effusion, especially when it is associated with relative bradycardia. Additional growth promoting therapy should be considered for incomplete catch-up growth in prolonged hypothyroidism during thyroxine supplementation.